Adaptive emotion regulation might prevent burnout in emergency healthcare professionals: an exploratory study - Krisztina Pálfi; Jutta Major; Andrea Horváth-Sarródi; András Deák; Gergely Fehér; Boróka Gács (BMC, 2024)
Abstract Background Emergency department (ED) professionals face a high risk of physical, mental, and emotional strain, which can lead to burnout. Burnout arises from chronic work-related stress, which negatively impacts ED professionals, the healthcare system, as well as patient outcomes. Effective adaptive emotion regulation strategies (ERS) are crucial for handling stress in healthcare workplaces and mitigating the risk of burnout. High-quality patient-professional relationships, including empathy, significantly improve patient compliance and disease outcomes. This cross-sectional exploratory study aims to investigate the relationship between mental distress, burnout, adaptive and maladaptive ERS among healthcare professionals in an ED. Methods A total of 159 ED workers participated in an online survey. Emotion regulation was assessed using the Cognitive Emotion Regulation Questionnaire, while burnout and mental distress were measured using the Maslach Burnout Inventory and the Depression, Anxiety, and Stress Scale. Results The findings revealed that more than 20% of participants displayed severe symptoms of stress (N = 35), anxiety (N = 36), and depression (N = 31), and only 10.7% (N = 27) had no signs of burnout. Despite these findings, it appears that the majority of ED professionals primarily utilise adaptive ERS (91.8%, N = 146). However, as burnout levels increased, the use of adaptive ERS declined compared to maladaptive strategies. Regression analysis identified several significant predictors of Emotional Exhaustion, Depersonalisation, and reduced Personal Accomplishment, including gender, age, physical exercise, smoking, sedative usage, stress, depression, maladaptive strategies and adaptive strategies such as positive reappraisal. Conclusions These study results highlight the urgent need to address workplace stress, burnout, and mental distress among healthcare professionals in EDs. Implementing effective strategies for adaptive emotion regulation and promoting a supportive work environment can help mitigate burnout and enhance the well-being of ED workers, ultimately benefiting patient care and outcomes.